City - Scale Spatial Data Infrastructure for Solar Photovoltaic Energy Generation Assessment - Gowri Shankar Rao, R; K. Rayaguru, N; G.Renganathan, N; Kumar Thakur, Sunil (International Journal of Engineering and Technology, 2018)
Spatial data plays an vital  role in decision-making for development of smart cities.  As it is very evident that  the development of   smart and sustainable city  mainly depends on its physical infrastructure such as intelligent transportation, smart energy, smart metering etc., This paper  provides an analysis  which aims  using the  spatial data infrastructure  tools  for estimation of  the  region  based  solar PV potential  generation  for a specific urban region . This analysis would afford a great insight in deciding a city scaled potential energy production and planning,  an estimate of the geographical PV potentials for solar power generation is adopted.  The total PV potential is evaluated for  a specific defined area and compared with the local electricity demand. The outcomes comprise of an initial valuation of the town's solar potential that can be used to upkeep organization decisions regarding reserves in solar systems.  Successful implementation of SDI  finally depends on the political governance and  their framing policies.